2001
DOI: 10.1074/jbc.m102417200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Matrix Metalloproteinases by Peroxynitrite-induced Protein S-Glutathiolation via Disulfide S-Oxide Formation

Abstract: Oxidative stress may cause tissue injury through activation of the precursors of matrix metalloproteinase (proMMPs). In this study, we observed glutathione (GSH)-dependent proMMP activation induced by peroxynitrite, a potent oxidizing agent formed during inflammatory processes. Peroxynitrite strongly activated all three types of purified human proMMPs (proMMP-1, -8, and -9) in the presence of similar concentrations of GSH. Of the potential reaction products between peroxynitrite and GSH, only S-nitroglutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
299
4
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(315 citation statements)
references
References 53 publications
6
299
4
3
Order By: Relevance
“…Full-length MMP9 is the major form of MMP9 in cancer tissues (Fridman et al, 2003) and in MDA-MB-231, an invasive breast cancer cell line. Several studies have suggested that without the participation of proteolytic enzymes and removal of the inhibitory peptide, full-length MMP9 can be activated by binding to the substrates to cause conformational changes or oxidative modification of the cysteine sidechain thiol groups, in turn allowing zinc ion to become available for the catalytic function (Okamoto et al, 2001;Bannikov et al, 2002;Gu et al, 2002). Transforming growth factor-b is a potent growth inhibitor of normal epithelial cells, but also fosters tumor formation during later stages of tumorigenesis (Wakefield and Roberts, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Full-length MMP9 is the major form of MMP9 in cancer tissues (Fridman et al, 2003) and in MDA-MB-231, an invasive breast cancer cell line. Several studies have suggested that without the participation of proteolytic enzymes and removal of the inhibitory peptide, full-length MMP9 can be activated by binding to the substrates to cause conformational changes or oxidative modification of the cysteine sidechain thiol groups, in turn allowing zinc ion to become available for the catalytic function (Okamoto et al, 2001;Bannikov et al, 2002;Gu et al, 2002). Transforming growth factor-b is a potent growth inhibitor of normal epithelial cells, but also fosters tumor formation during later stages of tumorigenesis (Wakefield and Roberts, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of studies have reported an inhibition of enzyme activity by glutathionylation, it appears that the position of the cysteine undergoing modification is important in determining the effect of glutathionylation. For instance, human immunodeficiency virus type 1 protease can be inhibited or stabilized by glutathionylation depending on which cysteine is involved (39), whereas matrix metalloproteinases are activated upon glutathionylation of the autoinhibitory domain (40).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of proMMPs is triggered by peroxynitrite generation via an extensive S-glutathiolation reaction. 29 By inhibiting this reaction, peroxynitrite decomposition catalysts may reduce MMP activation. In addition to direct oxidation, peroxidation, and nitration reactions and MMP activation, likely additional downstream cytotoxic mechanisms elicited by peroxynitrite during DOX-induced cardiac injury include DNA injury and activation of the nuclear enzyme poly(ADP-ribose) polymerase, as well as the inhibition of myofibrillar CK.…”
Section: Effects Of Fp 15 On Myocardial Damage Produced By Transient mentioning
confidence: 99%